Beneficios de suplementación de fitasa en dietas de producción de cerdos de engordes - Coello Vera, Álvaro Vinicio (2021)
The present study has to do with the benefits of phytase supplementation in fattening pig production diets. Adequate nutrition, essential for successful pig production, is one of the most important challenges in the sector, particularly with regard to the availability and cost of feed. In a commercial production unit, food represents between 60% and 70% of production costs: the efficient use of the resources available for food is therefore essential for the profitability of this type of unit. Therefore, the objectives were set: to collect information regarding phytase supplementation in fattening pig production diets and to determine the effects of phytase in fattening pig production diets. Where it was possible to analyze with the help of the investigations carried out that the phytase added in the diets for pigs in the growth phase, showed higher weights in relation to the control of the experiment, it also gives greater weight gain is achieved with the addition of phytase in the weeks, a better feed conversion is achieved with the addition of phytase in the diet, in the fourth week of the trial. Therefore, it is recommended to add balanced commercial use phytase + phytase (5%) to the diet in the growth phase of pigs.